2000
DOI: 10.1210/jcem.85.11.6956
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin and Sulfonylurea Therapy, at the Same Level of Blood Glucose Control, on Low Density Lipoprotein Subfractions in Type 2 Diabetic Patients1

Abstract: The aim of this study was to evaluate the effect of sc insulin (INS) compared with sulfonylurea (SUL) therapy, at the same level of blood glucose control, on the low density lipoprotein (LDL) subfraction profile in normolipidemic type 2 diabetic patients. Nine normolipidemic type 2 diabetic men (age, 56+/-3 yr; body mass index, 26.5+/-0.9 kg/m2; mean +/- SEM), after a 3-week wash-out period, were assigned to INS or SUL for 2 months in a randomized cross-over design. Doses were adjusted only during the first mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The present study showed no significant differences in BMI, marital status, or smoking between all groups, while diabetic patients need to consider the impact of obesity on developing microvascular complications. The present finding is supported by the Rivellese et al (2000) 26 study, which found no significant variation in the BMI being very similar at the end of each treatment period. In contrast, Doghish et al (2019) 12 found that the BMI of both patient groups was significantly different from the control group, but there was no significant difference between patient groups.…”
Section: Discussionsupporting
confidence: 88%
“…The present study showed no significant differences in BMI, marital status, or smoking between all groups, while diabetic patients need to consider the impact of obesity on developing microvascular complications. The present finding is supported by the Rivellese et al (2000) 26 study, which found no significant variation in the BMI being very similar at the end of each treatment period. In contrast, Doghish et al (2019) 12 found that the BMI of both patient groups was significantly different from the control group, but there was no significant difference between patient groups.…”
Section: Discussionsupporting
confidence: 88%
“…One study also observed an anti-diabetic effect on the erythrocyte membrane of diabetes mellitus individuals with alterations in glucose levels and lipid and phospholipid subtraction. 21 Many workers have observed lipid alterations in diabetes mellitus and hyperglycaemia, other metabolic alterations [40][41][42][43][44] This study demonstrated that pomegranate juice combined with an antidiabetic therapy regimen could provide additional benefits in glucose control. Phospholipids affect insulin action, ranging from altering gene expression linked to glucose absorption and affecting mitochondrial dynamics.…”
Section: Discussionmentioning
confidence: 91%